STUDENT PERCEPTIONS ABOUT THE NEWS OF THE DETERMINATION OF CORONAVIRUS (2019-nCoV) PANDEMIC INVASION AND THE NEW LIFESTYLE ORDER ON SOCIAL MEDIA INSTAGRAM - Yefi Dyan Nofa Harumike; Gede Dhana Saputra (Universitas Islam Balitar, 2023)
It’s been being public consumption globally the news about new disease that came from Wuhan, China. This also caused a lot of anxiety to the several levels of society. Because, the transmission of this disease is very fast. Its called severe acute respiratory syndrom (SARS) that has been appeared in mid-December 2019. This time it appear with a new form called SARS-CoV-2 as the caused of the Corona Virus Disease 2019 (Covid-19) pandemic which causes respiratory system disorder, acute pneumonia, until death. With the information that determines the percentage of virus transmission above make Indonesian people in particular experience excessive anxiety to the death will cause emotional dysfunction such neuroticism, depression, and psycosomatic disorder. With a massive news development of this Covid-19 everyday as the news headline, the government try to enforce the new normal policies that will no border to the public activity of course with the awarness of the health protocol. The perception that formed in to college student about the news of confirmation pandemic invasion of Novel Coronavirus (2019-nCoV) and new normal life on social media instagram between one to another was not the same because affected by several factors and caused some perception effect to the communicant. Such as cognitive effect, affection effect, and behavioral effect that surely affect to the their daily activity.